Adolescent mental health and subsequent parenting: a longitudinal birth cohort study. Issue 5 (19th December 2013) - Byford, M; Abbott, R A; Maughan, B; Richards, M; Kuh, D
Abstract : Background: Adolescent mental health problems are associated with a range of adverse outcomes in adulthood but little is known about the effects on adult parenting practices. This study aimed to examine prospective associations between adolescent conduct and emotional problems and subsequent parenting behaviours in adulthood. Methods: The study sample comprised 1110 members from the MRC National Survey of Health and Development. Prospective data were collected from teacher reports of conduct and emotional problems at age 13 and 15 years and adult outcome measures of parenting included intellectual environment, cognitive stimulation, coercive discipline, parental interest and parental aspiration. Results: In regression models adjusted for the confounding effects of social background, cognition and education, adolescent conduct problems predicted coercive parenting behaviours in adulthood. The effects of adolescent emotional problems on the development of coercive discipline practices were explained by covariates. Likewise, the inability of parents who displayed conduct problems in adolescence to provide an intellectually stimulating home environment was fully explained by the adjustment for education. Conclusions: Adolescents who exhibit conduct problems are more likely to develop coercive styles of parenting.